Harnessing implementation science to optimize harm prevention in critically ill children: A pilot study of bedside nurse CLABSI bundle performance in the pediatric intensive care unit. - Woods-Hill, Charlotte Z.; Papili, Kelly; Nelson, Eileen; Lipinski, Kathryn; Shea, Judy; Beidas, Rinad; Lane-Fall, Meghan (American Journal of Infection Control, 2021)
• Central-line associated bloodstream infections (CLABSIs) have serious negative consequences. • Compliance by nurses with a bundle to prevent CLABSI is suboptimal. • Implementation and behavioral science offer new insights into why compliance is challenging. • Strategies that facilitate opportunity and optimize motivation may improve bundle compliance. Central-line associated bloodstream infection (CLABSI) is associated with increased mortality, morbidity, and cost in hospitalized children. An evidence-based bundle of care can decrease CLABSI, but bundle compliance is imperfect. We explored factors impacting bundle performance in the pediatric intensive care unit (PICU) by bedside nurses. Single-center cross-sectional electronic survey of PICU bedside nurses in an academic tertiary care center; using the COM-B (capability, opportunity, motivation) and TDF (theoretical domains framework) behavioral models to explore CLABSI bundle performance and identify barriers to compliance. We analyzed 160 completed surveys from 226 nurses (71% response rate). CLABSI knowledge was strong (capability). However, challenges related to opportunity were identified: 71% reported that patient care requirements impact bundle completion; 32% described the bundle as stressful; and CLABSI was viewed as the most difficult of all bundles. Seventy-five percent reported being highly impacted by physician attitude toward the CLABSI bundle (motivation). PICU nurses are knowledgeable and motivated to prevent CLABSI, but face challenges from competing clinical tasks, limited resources, and complex family interactions. Physician engagement was specifically noted to impact nurse motivation to complete the bundle. Interventions that address these challenges may improve bundle performance and prevent CLABSI in critically ill children.